The nexus between domestic interests and foreign aid policy: the case of the Norwegian aid agenda - Bakkeskau, Benedicte (AUC Knowledge Fountain, 2011)
This thesis looks at the nature of Norwegian aid and how the domestic socio-political realities influence the character of Norwegian development assistance. Norwegian development aid is analyzed as a foreign policy decision, examining the institutional structure and domestic stakeholders and establishing the role and strength of each player within the decision-making process. Understanding how development policies are formed provides a better background for analyzing the interests that lies behind a country's aid program. In being aware of these interests, we can better analyze the donor motives of foreign aid and how they impact the development trajectory in the recipient country. The research yields several findings regarding the formation of Norway's development policy: 1) Norway has a corporative system where domestic actors actively take part in the decision-making process; 2) Domestic stakeholders participate when the issue at hand concerns their own agenda or affects them in any way; 3) Their strength within the system depend on whether or not they are aligned with the political agenda of the sitting government. The research further suggests that the individual has some impact on the policy process, though this largely depends on their position within the system. In conclusion, the research confirms that to a certain extent Norwegian development policy is influenced by domestic socio-political interests.